Peranan Self Efficacy Dalam Mengatasi Kecemasan Berbicara Di Depan Umum - Ariane Nafila; Syamsu Al Alam Al Fatah (Muttaqien, 2022)
This study is a literature research that aims to determine the factors that cause anxiety when speaking in public and to offer the concept of self efficacy as a solution in overcoming public speaking anxiety on the subject. The subjects of this study were 33 students of Institut Agama Islam Az-Zaytun Indonesia (IAI AL-AZIS) aged between 18 to 22 years, and according to the criteria that determined by the author. The data collection method used for this research is a closed questionnaire method. The results obtained in this study indicate that: (1) there are physical and psychological symptoms experienced by partisipants when they are about to or are speaking in public; (2) there are several factors that cause public speaking anxiety; (3) self efficacy is the solution offered by the author in overcoming public speaking anxiety for students.